Toward muzakki: Reconstructing a digital-ready productive zakat ecosystem through an integrated four-pillar model - Chamid, Abdul; Nurlaeli, Ida; Olasunkanmi, Emiola Habeeb; Abdus-salaam, Habeebullah (Indonesian Journal of Islamic Economics Research, 2026)
Productive zakat management in Indonesia is constrained by a persistent gap between its estimated potential and low realization, compounded by the absence of impact-based evaluation and limited integration with digital ecosystems. Prior studies remain fragmented, focusing mainly on economic outcomes, lacking an integrated transformation model, and overlooking the munfiq stage as a critical transition phase. This study addresses these gaps by reconstructing a digitally ready, productive zakat ecosystem to accelerate the transformation from mustahik to muzakki. Using a constructivist qualitative approach with a single case study at BAZNAS Banyumas Regency, data were collected through in-depth interviews, participatory observation, and document analysis, and analyzed using the Miles–Huberman–Saldaña interactive model. Findings reveal a pronounced execution gap, particularly in implementation and evaluation, resulting in partial achievement: beneficiaries consistently reach the munfiq stage but fail to transition to verified muzakki status. This reflects systemic weaknesses in sustained mentoring, outcome-based evaluation, and integrated data tracking. This study advances the literature by proposing the Integrated Four-Pillar Transformation Model, spiritual-ethical, managerial-strategic, economic-business, and social-mentoring, and by positioning the munfiq stage as a decisive inflection point in the transformation pathway. Policy implications emphasize the urgency of adopting outcome-based evaluation systems, institutionalizing structured mentoring, and developing digitally integrated zakat ecosystems enabling data-driven monitoring, scalable empowerment, and real-time impact measurement.